P5.093 Evaluation of a New Amplified DNA Assay on the Becton Dickinson Viper System in Extracted Mode For the Detection of Trichomonas Vaginalis from Vaginal Specimens. (13th July 2013) - Pol, B Van Der; Williams, J A; Eddleman, L; Fuller, D; Taylor, S; Schwebke, J; Lebed, J; Smith, B; Nye, M; Gaydos, C
Abstract : Background: The BD ProbeTec TM Trichomonas vaginalis (TV) Q x amplified DNA Assay (TVQ) is a new test for qualitative detection of TV DNA that can be performed on the automated BD Viper System. The objective of this study was to compare the performance of this new assay to a patient infected status (PIS) and to an FDA approved molecular assay using vaginal swabs. Methods: Vaginal swabs were obtained from women attending STD or family planning clinics at 7 sites. A patient collected vaginal swab was tested by TVQ; APTIMA TV (ATV) testing was performed using a clinician obtained vaginal swab according to the package insert. Additional clinician obtained vaginal swabs were used for wet mount and culture. A patient was considered infected if either the wet mount or culture was positive for TV and not infected if both tests were negative. Agreement between the TVQ and ATV assays was assessed using Kappa statistics. Results: Data were available for TVQ evaluation from 838 women, 116 of whom were defined as infected with TV. Despite being in the definition of the PIS, wet mount still had a sensitivity of only 68.7% which was statistically lower than the other assays (p < 0.001). TVQ sensitivity and specificity estimated based on the PIS were 94.2% and 99.7%, respectively. TVQ performed similarly to the ATV assay (κ = 0.938). Conclusions: The TVQ assay performed significantly better than wet mount and had comparable sensitivity and specificity to an FDA approved molecular assay for the detection of TV. This study provides additional evidence of the poor performance of wet mount for TV. The use of patient collected vaginal swabs for the detection of TV DNA provides clinicians with the opportunity to increase efficiency within the clinic while obtaining improved results over wet mount.